Exploring the User Experience of E-Thesis System: An Evaluation Using UX Honeycomb Method - wahyu hariyanto (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2022)
This research article discusses the evaluation of the e-thesis information system in the Library and Information Science program at UIN Maulana Malik Ibrahim Malang. The background of this research is that the system is relatively new and is supported by several preliminary surveys conducted among users, most of whom are unfamiliar with the use of this e-thesis application system. The research population was taken from all students of the Library and Information Science Department in the 2018 and 2019 academic years, with a research sample of 50 students. The honeycomb method was used as the analysis tool for the evaluation, which emphasizes how UX can go beyond just usability aspects for users. The assessment aspects in the honeycomb method include useful, usable, desirable, findable, accessible, credible, and valuable. The research results showed that the overall average value of the e-thesis information system was 4.10, indicating that the e-thesis system is considered good in terms of its use. The highest score of 4.23 was found in the useful aspect, indicating that students agreed that the e-thesis information system could solve user problems and meet their needs. The lowest score of 3.93 was found in the accessible aspect, which needs improvement for future development of the information system. Indicators that need attention for improvement include less appealing design and the need to enhance capabilities. Suggested improvements include visual design, an advance search button, display of two thesis advisors, UI refresh, minimizing errors, and detailed schedule display on the homepage. Improving the existing features according to the research conducted can have a wide impact on the use of the information system and can be used continuously without errors.